Comparative noise performance of a coded aperture spectral imager - Piper, Jonathan; Yuen, Peter W. T.; Godfree, Peter; Ding, Mengjia; Soori, Umair; Selvagumar, Senthurran; James, David (SPIE - International Society for Optics and Photonics, 2016)
Novel types of spectral sensors using coded apertures may offer various advantages over conventional designs, especially the possibility of compressive measurements that could exceed the expected spatial, temporal or spectral resolution of the system. However, the nature of the measurement process imposes certain limitations, especially on the noise performance of the sensor. This paper considers a particular type of coded-aperture spectral imager and uses analytical and numerical modelling to compare its expected noise performance with conventional hyperspectral sensors. It is shown that conventional sensors may have an advantage in conditions where signal levels are high, such as bright light or slow scanning, but that coded-aperture sensors may be advantageous in low-signal conditions